KADAR HEMOGLOBIN (HB) IBU HAMIL PRE DAN POST PEMBERIAN TABLET ZAT BESI (FE) DI UPTD PUSKESMAS KECAMATAN SANANWETAN KOTA BLITAR - Sunarti Sunarti (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2020)
Background: Anemia occurs due to a lack of iron intake (Fe) in foods consumed by the marked hemoglobin (Hb) rate below 11 g/dL. In district health Sananwetan Blitar implement the program of giving iron tablet (Fe) to pregnant mother as one effort to increase hemoglobin (Hb) as anemia prevention.Purpose: The general purpose of this research is to know the change of hemoglobin (Hb) rate of pregnant mother pre and post iron tablet (Fe) in district health Sananwetan Blitar.Method: The research method used is descriptive research. The population in this study were 76 with 31 samples of pregnant mother. Results: The data were collected from 25 February to 31 March 2017. The result of this study was an abnormal hemoglobin (Hb) rate of 74.2% (23 pregnant mother) before iron tablet (Fe) and after iron tablet (Fe) normal hemoglobin (Hb) is 77.4% (24 pregnant mother). With an average increase in hemoglobin (Hb) rate of pre and post pregnant mother is 1.1 g / dL.Conclusion: Provision of iron tablets (Fe) in pregnant mother can increase hemoglobin (Hb). Provision of iron tablets can increase hemoglobin (Hb) rate of pregnant mother. Recommendation for health personnel district health Sananwetan Blitar that is giving the right information to pregnant mother about the importance of iron tablet (Fe).